(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. Nephrolithiasis is one of the most common urinary tract diseases. After the first episode of urinary calculus, the risk of recurrence is nearly 40% to 50% at 5 years. Nephrolithiasis is a systemic disease that is associated with some metabolic disorders. This study aimed to provide a picture of the frequency of metabolic abnormalities in patients with nephrolithiasis from west part of Iran. Materials and Methods. Patients with recurrent urinary tract calculi referred to the Nephrology-Urology Clinics in Khorramabad city were recruited. After collection of demographic data of all the patients, 24-hour urine and blood samples were taken to measure biochemical factors. Results. Of the 232 participants, 125 were males and 107 were females. Hyperoxaluria was seen in 93 (40.1%) of the participants, hypercalciuria in 55 (23.7%), hypocitraturia in 58 (25%), and hyperuricosuria in 33 (14.9%). Hyperoxaluria in the males was significantly more frequent than in the female patients. There were no significant differences between the two groups in other urinary metabolic disorders. Conclusions. Patients with nephrolithiasis from Lorestan province may have metabolic characteristics varying from those of regions; ethnicity may be a possible reason. Variation of dietary regimens, such as the amount of meat or vegetable in the diet that can change oxalate, calcium, or citrate of urine, might have influenced the results. Time of sampling is another factor. Population-specific studies are helpful to health care providers for preventive planning for nephrolithiasis.